BILLING LEARNING AS A FACTOR OF SUCCESSFUL PROFESSIONAL ADAPTABILITY - Пришупа, Ю. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article deals with the conceptual theoretical aspects of bilinguing education in technical universities. Peculiarities of bilingual orientation development as necessary component of professional adaptability are analyzed. The article defines the problems of formation of professional adaptability as dynamic quality of personality. In addition, it is defined as a meaningful characteristic of professional adaptability and distinguished ways of its formation. The purpose of this article is to consider the existing theoretical approaches to the bilingual education determination, to highlight the peculiarities and problems of bilingual training of future specialists of technical direction in the process of professional adaptability. In the article the specific peculiarities of the sequence and stages of adaptive specialist, delineated qualities, personal characteristics which are professionally significant and necessary for successful professional activity of technical specialists have been characterized. The author substantiated the importance of forming professional adaptability for future specialists of technical direction in the university to carry out competitive activity in the future, as well as reveals the essence of bilingual training that lies in the interdisciplinary phenomenon of professional training of future specialists.. Therefore, considering the training of future specialists in the technical field, it is necessary to focus on bilingual training as a component of professional growth of the specialist in the technical field, as well as to create a system of professional skills that allow to achieve professional adaptability, self-realization, acquisition of a professional culture of communication, readiness and ability to work successfully in the context of intercultural communication.